Predictive value of brain and vascular imaging including intracranial vessels in transient ischaemic attack patients: external validation of the ABCD3‐I score. Issue 7 (26th March 2013) - Purroy, F.; Jiménez‐Caballero, P. E.; Mauri‐Capdevila, G.; Torres, M. J.; Gorospe, A.; Ramírez Moreno, J. M.; de, N. P.; Cánovas, D.; Arenillas, J.; Álvarez‐Sabín, J.; Martínez Sánchez, P.; Fuentes, B.; et al.
<x xml:space="preserve">Abstract</x> Background and purpose Recently, brain and vascular imaging have been added to clinical variables to identify patients with transient ischaemic attack (TIA) with a high risk of stroke recurrence. The aim of our study was to externally validate the ABCD3‐I score and the same score taking into account intracranial circulation. Methods We analyzed data from 1137 patients with TIA from the PROMAPA study who underwent diffusion‐weighted magnetic resonance imaging (DWI) within 7 days of symptom onset. Clinical variables and diagnostic work‐up were recorded prospectively. The end‐points were subsequent stroke at 7 and 90 days follow‐up. Results A total of 463 (40.7%) subjects fulfilled all inclusion criteria. During follow‐up, eight patients (1.7%) had a stroke within 7 days, and 14 (3.1%) had a stroke within 3 months. In the Cox proportional hazard multivariate analyses, the combination of large‐artery atherosclerosis and positive DWI remained as independent predictors of stroke recurrence at 7‐ and 90‐day follow‐up [HR 8.23, 95% confidence interval (CI) 2.89–23.46, P < 0.001]. The ABCD3‐I score was a powerful predictor of subsequent stroke. The area under the receiver operating characteristic curve was 0.83 (95% CI 0.72–0.93) at 7 days and 0.69 (95% CI 0.53–0.85) at 90 days. When we include intracranial vessel disease in the score, the area under the curve increases but the difference observed was non‐significant. Conclusion The inclusion of vascular and neuroimaging information to clinical scales (ABCD3‐I score) provides important prognostic information and also helps management decisions, although it cannot give a complete distinction between high‐risk and low‐risk groups.